2013
DOI: 10.5021/ad.2013.25.4.405
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Serum Zinc and Copper Concentrations in Hair Loss

Abstract: BackgroundIt is well known that some trace elements such as zinc and copper play a significant role in many forms of hair loss. However, the effect of zinc and copper in the pathogenesis of hair loss is still unknown.ObjectiveThe purpose of this study is to evaluate the zinc and copper status in each of four types of hair loss.MethodsA study was carried out with 30 health controls and 312 patients who were diagnosed with alopecia areata (AA), male pattern hair loss, female pattern hair loss and telogen effluvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
82
5
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(98 citation statements)
references
References 18 publications
8
82
5
3
Order By: Relevance
“…In support of this association, some past studies have found no decreased serum Zn levels in AA patients [76][77][78]. In contrast, in the 2000s, several studies found decreased serum Zn levels in AA patients [60,[79][80][81][82].…”
Section: Accepted Manuscriptmentioning
confidence: 89%
See 1 more Smart Citation
“…In support of this association, some past studies have found no decreased serum Zn levels in AA patients [76][77][78]. In contrast, in the 2000s, several studies found decreased serum Zn levels in AA patients [60,[79][80][81][82].…”
Section: Accepted Manuscriptmentioning
confidence: 89%
“…Accordingly, patients with telogen effluvium even without AE show lower serum Zn concentrations than healthy controls [59,60], with the condition being cured by oral Zn supplementation [59]. In AE patients, decreased Zn concentration is also observed in hair [61].…”
Section: Alopecia In Aementioning
confidence: 98%
“…Signs of deficiency include growth retardation, delayed puberty, diarrhea, alopecia, glossitis, nail dystrophy, and decreased immunity among others [95]. Low zinc levels have been identified in patients with AA, AGA, and TE [96]. Proposed mechanisms for zinc-associated hair regrowth include antimicrobial, anti-inflammatory, antioxidant, and anti-5α-reductase activity [97][98][99][100].…”
Section: Zincmentioning
confidence: 99%
“…The idea that zinc deficiency may interfere with hair growth has emerged since the 1990s. [7] Although some studies have reported that zinc deficiency correlates with alopecia areata (AA) and telogen effluvium (TE), there are no studies have examined the relationship between zinc and androgenic alopecia so far. This study is important because there are no studies that examine the relationship between zinc levels with androgenic alopecia.…”
Section: Introductionmentioning
confidence: 99%